Cinema and Agamben: ethics, biopolitics and the moving image - Gustafsson, Henrik; Grønstad, Asbjørn (Bloomsbury, 2014)
A collection of original essays that bring together a group of established and emerging scholars of film and visual culture for an innovative study of contemporary film theory and philosophy. Refracting current conceptions of the moving image through the influential work of Italian philosopher Giorgio Agamben, these essays facilitate a unique multidisciplinary conversation that rethinks the theory of and praxis of cinema. In their resourceful analyses of the work of artists such as David Claerbout and Marcel Duchamp, the authors put to use a number of the key concepts from Agamben's rich work: biopolitics, de-creation, dispositif, gesture, the messianic, and profanation, to name a few.